Lactoferrin-modified Betulinic Acid-loaded PLGA nanoparticles are strong anti-leishmanials. (October 2018) - Halder, Asim; Shukla, Divanshu; Das, Suvadra; Roy, Partha; Mukherjee, Arup; Saha, Bhaskar
Highlights: Betulinic acid (BA) is a potential anti-leishmanial compound. BA delivery by lactoferrin-PLGA nanoparticle enhances its anti-leishmanial effects. Lf-BANPs lower IL-10 but enhance iNOS expression to exert anti-leishmanial effects. Abstract: Visceral Leishmaniasis (VL), caused by the protozoan parasite Leishmania donovani, is a potentially fatal disease. The only orally bioavailable drug miltefosine is toxic and the effective liposomal Amphotericin B (AmBisome) is limited by its prohibitive cost and requirement for parenteral administration. Therefore, finding a new potential drug candidate and an alternative delivery system is imperative. We report that Betulinic acid (BA), a pentacyclic triterpenoid from Betula alba bark, was loaded onto uniformly spherical PLGA nanoparticles (BANPs; diameter 187.5 ± 5.60 nm) coated with Lactoferrin (Lf-BANPs). The amastigotes count in macrophages was more effectively reduced by Lf-BANP than BA and BANP. Lf-BANPs reduced the pro-parasitic, anti-inflammatory cytokine IL-10, but increased nitric oxide (NO), production in L. donovani -infected macrophages indicating that Lf-BANP possesses a significant anti-leishmanial activity.